Tobacco Transcription Factor WRKY1 Is Phosphorylated by the MAP Kinase SIPK and Mediates HR-Like Cell Death in Tobacco - Frank L. H. Menke; Hong-Gu Kang; Zhixiang Chen; Jeong Mee Park; Dhirendra Kumar; Daniel F. Klessig (Molecular Plant-Microbe Interactions, 2005)
The salicylic acid-induced protein kinase (SIPK) of tobacco, which is a mitogen-activated protein kinase (MAPK), is activated by various biotic and abiotic treatments. Overexpression of SIPK has been shown to trigger cell death. In this study, a targeted yeast two-hybrid approach identified the tobacco transcription factor WRKY1 as a potential substrate. SIPK phosphorylated WRKY1, which resulted in enhanced DNA-binding activity of WRKY1 to its cognate binding site, a W box sequence from the tobacco chitinase gene CHN50. SIPK-mediated enhancement of WRKY1 DNA-binding activity was inhibited by staurosporine, a general kinase inhibitor. Co-expression of SIPK and WRKY1 in Nicotiana benthamiana led to more rapid cell death than expression of SIPK alone, suggesting that WRKY1 is involved in the formation of hypersensitive response-like cell death and may be a component of the signaling cascade downstream of SIPK.